Transdisciplinarity in Old and New Concepts for Novel Physiotherapies - Adela-Madgalena Ciobanu; Sorin Riga; Dan Riga (Highlights on Medicine and Medical Research Vol. 7, 2021)
This book chapter deals with Transdisciplinarity in Old and New Concepts for Novel Physiotherapies.